FAKTOR – FAKTOR YANG MEMPENGARUHI PERILAKU WAJIB PAJAK ORANG PRIBADI TERHADAP PENGGUNAAN E-FILING - Fitri Apriani; Syafrida Hani (Universitas Medan Area, 2016)
The purpose of this study to examine the factors that influence faktr wajibpajak individual behavior towards the use of e-filing on STO Medan Belawan. Methods of sample selection using a convenience sampling. From the results of the test T is known that the technology readiness variables significantly influence the use of e filling, while the security and confidentiality of variables, perceived usefulness and ease of no significant impact on the use of e-filing. From the results of the F test found no effect of technology readiness, security and confidentiality, perceived usefulness, and perceived ease of the use of e-filing on STO Medan Belawan.